Sistem Informasi Monitoring Distribusi Penerimaan Zakat Pada Badan Amil Zakat Nasional (Baznas) Kota Baubau - Israwan, LM. Fajar; Sabirin, Abdul Rasyid; Aprilia, Aprilia (Informatics Engineering Department, Dayanu Ikhsanuddin University, 2025)
Zakat management in Indonesia plays a crucial role in improving community welfare and reducing poverty. At BAZNAS Baubau City, the distribution process is still managed manually and lacks proper documentation, which limits transparency and accountability to the public. To address these issues. This study aims to design and develop a web-based zakat receipt distribution monitoring information system that facilitates centralized and real-time recording, reporting, and monitoring of zakat distribution. The system development methodology employed software development approaches using PHP, MySQL, Laravel Framework, and data collection techniques such as observation, interviews, and literature studies. The developed system underwent black box testing to ensure its functionalities meet user requirements. The research results indicate that the system significantly assists BAZNAS in monitoring zakat distribution, accelerates report generation, and enhances transparency in zakat management to the public. This system is expected to help BAZNAS Baubau City increase public trust and optimize zakat fund management efficiently.